Manghopol:Pendampingan Keindonesiaan terhadap Orang Sakit di Kabupaten Humbang Hasundutan - Purba, Sanny (JURNAL DIAKONIA, 2023)
Manghopol is a ritual performed to provide consolation to people who are grieving. In his understanding, Manghopol is embracing or providing comfort to someone who experiences disturbances in the three components of human life as previously explained. In general, the main aspect that is carried out in the manghopol ritual is giving boras si pir ni tondi. In his understanding, Boras si pir ni tondi is a medium for the Batak people to provide assistance to grieving people. boras si pir ni tondi means that the person who receives the rice is prayed for to become na bolon to give a strong tondi in dealing with his grief.